Fluid, Electrolyte and Acid-Base Disorders Clinical Evaluation and Management - Reddi, Alluru S. (Springer New York : Imprint: Springer, 2014)
Fluid, Electrolyte and Acid-Base Disorders: Clinical Evaluation & Management  is a clear and concise presentation of the fundamentals of fluid, electrolyte and acid-base disorders frequently encountered in clinical practice.   Each chapter begins with pertinent basic physiology followed by its clinical disorder. Cases for each fluid, electrolyte and acid-base disorder are discussed with answers.  In addition, board-type questions with explanations are provided for each clinical disorder to increase the knowledge for the clinician. Practical and clinically oriented, this book is a handy reference for practicing physicians, students, residents and fellows.